Weak VLPP and MUCP correlation and their relationship with objective and subjective measures of severity of urinary incontinence - Martan, A; Masata, J; Petri, E; Svabík, K; Drahorádová, P; Voigt, R; Pavlíková, M; Hlásenská, J (International urogynecology journal and pelvic floor dysfunction, 2007)
The aims of the present study were to find the correlation between Valsalva leak-point pressure (VLPP) and cough leak-point pressure (CLPP) and to determine whether the water perfusion maximum urethral closure pressure (MUCP) correlates with VLPP. Seventy-nine women with previously untreated stress urinary incontinence were recruited to participate in a clinical study. Their mean age was 56.4 years, mean BMI was 27.8, and mean parity was 1.9. The mean values of VLPP and CLPP were 50.4 and 52.9 cm H(2)O, respectively. We did not find statistically significant differences in the mean values of VLPP and CLPP. The mean value of MUCP at rest was 44.2 cm H(2)O and the mean value of MUCP during maximal Valsalva maneuver was 37.2 cm H(2)O; with 500 ml of sterile saline in the bladder the difference between them is statistically significant. In the study group (n=79), 56 patients (77%) had low VLPP (< or =60 cm H(2)O), 21 patients (30%) had low MUCP (< or =30 cm H(2)O), and 8 patients had MUCP< or =20 cm H(2)O (all at rest). Of the 56 patients with low VLPP, 16 also had a low MUCP (< or =30 cm H(2)O). This study mainly compares two parameters-the MUCP and the VLPP. Based on our results we can conclude that there is no correlation between these parameters. MUCP measures urethral resistance at rest and VLPP measures urethral resistance during increased intra-abdominal pressure (Valsalva maneuver).
Keywords: Middle Aged; uretra; Urinary Incontinence; ženské pohlaví; stupeň závažnosti nemoci; tlak; dospělí; Humans; Adult; Pressure; Female; Urethra; inkontinence moči; Severity of Illness Index; lidé; lidé středního věku